Financial risk manager handbook plus test bank : FRM Part I/Part II - Jorion, Philippe , 1955- (John Wiley & Sons, 2011)
The essential reference for financial risk management Filled with in-depth insights and practical advice, the Financial Risk Manager Handbook is the core text for risk management training programs worldwide